Exploring hypoxia-related genes as prognostic indicators in lung adenocarcinoma - Bandar Alghamdi; Sonia Rocha (PLoS ONE, 2026)
Background Lung adenocarcinoma (LUAD) is a leading cause of cancer-related mortality, with hypoxia contributing to tumor progression and treatment resistance. Identifying hypoxia-related biomarkers could enhance prognosis and therapeutic strategies for LUAD. Methods This study aimed to identify hypoxia-related differentially expressed genes (HRDEGs) in lung adenocarcinoma (LUAD) through differential expression analysis. Functional analysis and protein-protein interaction (PPI) network construction were performed to explore the biological roles and interactions of these genes. Kaplan-Meier survival analysis, univariate Cox regression, and Lasso regression were used to identify key genes associated with survival. Multivariate Cox regression was then conducted to assess independent prognostic factors. Results This analysis revealed 283 upregulated HRDEGs and 322 downregulated HRDEGs in LUAD. Functional enrichment analysis indicated that the upregulated genes were primarily involved in cancer-related and cellular signaling pathways, while downregulated genes were associated with immunity-related pathways. We further identified 201 common upregulated hub genes (including MMP9, CDH1, HSP90AB1, SOX2, CDKN2A, SPP1, EZH2 ) and 224 common downregulated hub genes (such as IL6, TNF, IL1B, JUN, CCL2, TLR4, FOS, PTGS2 ). Kaplan-Meier survival analysis, univariate Cox regression, and Lasso regression led to the identification of 17 key genes ( ADRB2, ALDH2, CAT, CCNE1, MAP3K8, DSG2, EIF6, ABCB1, PIK3R1, RAD51, SFTPD, SOD3, CLEC3B, ADAM12, EXO1, FBLN5, and IGF2BP3 ) associated with patient survival. Finally, multivariate Cox regression analysis identified DSG2, EIF6, and EXO1 as independent prognostic factors for LUAD, highlighting their potential as biomarkers for prognosis and therapeutic targets in lung cancer. Conclusion In conclusion, DSG2, EIF6, and EXO1 were identified as key hypoxia-related genes in lung adenocarcinoma. These genes were found to be independent prognostic factors, highlighting their potential as biomarkers for predicting patient survival and guiding future therapeutic approaches.